Influence of elastomeric and steel ligatures on periodontal health during fixed appliance orthodontic treatment: a systematic review and meta-analysis - Umar Hussain; Alessandra Campobasso; Muhammad Noman; Shamsul Alam; Rida Mujeeb; Sofia Shehzad; Spyridon N. Papageorgiou (Progress in Orthodontics, 2024)
Abstract Introduction Metallic and elastomeric ligatures are widely used in orthodontics to secure the archwire within the bracket slots, but elastomeric ligatures have traditionally been associated with increased microbial colonization, which could adversely affect periodontal health. Aim This systematic review compares the periodontal effects of elastomeric and steel ligatures used for orthodontic fixed appliances. Methods Unrestricted literature search of 7 databases (MEDLINE, Scopus, Web of Science, Embase, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, and Virtual Health Library) up to July 2023 were performed for randomized / non-randomized clinical studies on humans comparing the two ligation methods during fixed-appliance therapy. After duplicate study selection, data extraction, and risk-of-bias assessment with the Risk of Bias (RoB) 2 or the Risk Of Bias In Non-randomized Studies - of Interventions (ROBINS-I) tool, random-effects meta-analyses of Mean Differences (MD) or Standardized Mean Differences (SMD) and their 95% confidence intervals (CIs) were carried out, followed by assessment of certainty of existing evidence with the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) approach. Results A total of 11 studies (3 randomized / 8 non-randomized) with 354 patients (mean age 14.7 years and 42% male) were included. No statistically significant differences were seen for plaque index (5 studies; SMD = 0.48; 95% CI = -0.03 to 1.00; P = 0.07), gingival index (2 studies; MD = 0.01; 95% CI = -0.14 to 0.16; P = 0.89), probing pocket depth (2 studies; MD = 0; 95% CI = -0.17 to 0.16; P = 0.97), or Streptococcus mutans counts (4 studies; SMD = 0.40; 95% CI=-0.41 to 1.20; P = 0.21). Elastomeric ligatures were associated with moderately increased total bacterial load (3 studies; SMD = 0.43; 95% CI = 0.10 to 0.76; P = 0.03). Confidence in these estimates was low in all instances due to the inclusion of non-randomized studies with high risk of bias. Conclusions Existing low quality evidence indicates that ligature method does not seem to influence the periodontal health during fixed treatment, even if elastomeric ligatures are associated with a moderate increase of bacterial load. Registration PROSPERO (CRD42023444383)